.M. Language features of the song "Kanshaubiy," or "Crying of princess Goshayah" - Mariam A. Akhmatova; Mahti Z. Ulakov; Sahadin M. Khubolov (Кавказология, 2024)
This article examines the linguistic features of the song “Kanshaubiy,” or “Crying Princess Goshayah.” Folklore is known to be invaluable material for research in linguistics, ethnography, and linguopholkloristics. In the text of this song, lexical and pictorial expressive means are used to represent the imagery and colorfulness of the language of the work. The study discovered that the linguocultural aspect of this song is expressed through comparative constructs, epithets, metaphor, phraseological turns, paroemias, benevolence, and potion. The onomastic lexicon of the song was then identified and described, as were various thematic groups, confirming the richness of the lexical composition of this work’s language. It should be noted that the song “Kanshaubiy,” or “Crying of Princess Goshayah,” traces various customs, traditions, and morals of the Karachay-Balkarian ethnic group, its mental foundations and everyday life, as well as some aspects of people’s lives.